NiAl Layered Double Hydroxide/Rice Husk Composite for the Efficient Removal of Malachite Green - Neza Rahayu Palapa; Tarmizi Taher; Normah Normah; Aldes Lesbani (Indonesian Journal of Chemistry, 2022)
Rice husk biochar (BC) loaded NiAl layered double hydroxide (LDH) has been synthesized to form NiAl LDH/BC composite through a co-precipitation method. NiAl LDH/BC has been used as an adsorbent to remove malachite green from water efficiently. The specific surface area analysis revealed that the surface area of NiAl LDH/BC composite increased five times, from 92.6 to 438.9 m2/g, compared to the original NiAl LDH. The adsorption studies revealed that NiAl LDH/BC composite followed the pseudo-second-order kinetic adsorption model while the isotherm followed the Langmuir monolayer adsorption model. The maximum adsorption capacity of NiAl LDH/BC composite prepared with a ratio of 1:1 and 1:0.5 achieved 185.1 mg/g and 142.9 mg/g, respectively, which is twice higher than the pristine ones (NiAl LDH). The thermodynamic parameters, determined at 303, 313, 323, and 333 K, revealed that the adsorption process was spontaneous and endothermic. The NiAl LDH/BC composite was tested for three consecutive adsorption-desorption cycles to investigate its reusability performance. It is found that their adsorption performance slightly decreased to 71.8% and 68.3% for NiAl LDH/BC composite 1:0.5 and 1:1, respectively. Therefore, it could be considered that the synthesized NiAl LDH/BC exhibited a good and efficient adsorbent for malachite greed removal.